Sistem Informasi Manajemen Keuangan Dana Bantuan Operasional Sekolah (Bos) melalui Aplikasi Rencana Kegiatan dan Anggaran Sekolah (ARKAS) di SDN 1 Kabunderan - Susanti Sangidah; Ali Muhdi (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
This study aims to examine the implementation of School Operational Assistance (BOS) Financial Management Information System through the School Activity and Budget Plan Application (ARKAS) at SD Negeri 1 Kabunderan, Karanganyar District, Purbalingga Regency. The research employed field research method with a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and documentation involving school principals, BOS treasurers, ARKAS operators, teachers, and school committees. Data analysis used Miles and Huberman's interactive model comprising data reduction, data presentation, and conclusion drawing. The findings indicate that ARKAS implementation encompasses four stages: budget planning, budget execution, financial administration, and reporting and accountability. ARKAS has been proven to enhance the effectiveness, efficiency, transparency, and accountability of BOS fund management. Nevertheless, several challenges remain, including internet connectivity disruptions, limited digital competency among school personnel, and administrative difficulties in data entry. Strategies to address these challenges include continuous technical training, infrastructure strengthening, and enhanced internal monitoring.